(untitled) (Journal of Oriental Studies, 2023)
Under the influence of the priests of Egyptian god Khnum’s temple the Egyptians destroyed the temple of Yaho which was located in Elephantine. In this clash Antisemitism had been seen for decades in professional literature. But the attack of Egyptians against Judeans was a political action and coincided with anti-Persian wave. There were different motives in the destruction of the temple in Elephantine. The spiritual élite of Jerusalem was for the destruction of the temple so they incited the Egyptians to take action. That clash was convenient also for the Egyptians cause besides religious and economic intolerance the anti-Persian revolt was increasing. The Persian satrapic regime didn’t suppress the Egyptians’ actions cause they didn’t have enough forces for that but tried to satisfy the complaints of Judeans in future allowing them to rebuild the temple. Thus, there was no reason to connect the destruction of the temple in Elephantine with the antisemitism.